Challenges and Strategies of English Language Teaching Within the Freedom-to-Learn Curriculum in Indonesia - Mlathi Paramesthi; Tono Suwartono (Proceedings Series on Social Sciences & Humanities, 2023)
The so-called â€œFreedom-to-Learnâ€ Curriculum has been implemented in Indonesia. However, in its application, the teachers seemed to face some challenges in executing their teaching plans. The aim of this research is to examine the challenges encountered by junior high school English teachers in the town of Banyumas, Indonesia, and to explore the strategies used by the teachers to confront the challenges. This is qualitative research that uses interviews, observations, and documents to collect the data. The study revealed that there are some challenges faced by the teachers: lack of understanding of the concept, lack of preparation, learning loss, big class size, and adjustment of a simultaneous summative test. Although there are some challenges, the learning process must continue. Therefore, the teachers used some strategies to meet the challenges: taking training, attending an English Teachersâ€™ Association meetings, creating an exciting and enjoyable learning environment, implementing the differentiated learning, and conducting an evaluation. The Freedom-to Learn Curriculum provides flexibility to educators to create quality learning that suits the needs and learning environment of students. Although the reality shows that it has not reached the curricular goal yet, all parties have tried to do their best.